Registration and characteristics of clinical trials on traditional Chinese medicine and natural medicines for endometriosis: a comprehensive analysis - Zhao, Yi; Wang, Yike; Xue, Zhu; Weng, Yuanyuan; Xia, Cencan; Lou, Jingyang; Jiang, Minmin (Frontiers in Medicine, 2024)
Objective To investigate the characteristics of clinical trials on traditional Chinese medicine (TCM) or natural medicines for treating endometriosis, aiming to inform future clinical practice and the development of new effective drugs. Method The global clinical trial registration platform was searched to identify clinical trials investigating the efficacy of TCM/natural medicine in treating endometriosis. Relevant trials were selected based on stringent inclusion and exclusion criteria. Data entry was performed using Microsoft Excel, while data analysis was conducted using SPSS version 23. Results The study encompassed 57 trials, of which ClinicalTrials.gov accounted for 18, ChiCTR for 3, ICRP for 15, and ChiDTR for 21 trials. The number of registrations showed a significant positive correlation with the years. Of the 57 clinical trials, 87.7% were randomized, 63.2% were blinded, 78.9% followed a parallel intervention model, and 56.1% had a sample size below 100. Regarding trial phases, 45.6% of clinical trials did not specify a phase, while Phase 3 and Phase 4 clinical trials accounted for 17.5%. Nine clinical trials involved drugs that are already on the market, including six Chinese patent medicines: Sanjie Zhentong Capsules, Honghua Ruyi Pills, Huayu Sanjie Enema Liquid, Kuntai Capsules, Wenjing Tang, and Xuefu Zhuyu Capsules. Outside China, Iran has the highest number of registrations for natural medicine treatments for endometriosis, with curcumin being the most registered natural medicine. Conclusion The analysis reveals that clinical trials on TCM and natural remedies for endometriosis often utilize randomization; however, substantial deficiencies remain in blinding and sample size adequacy. These findings suggest that, despite growing interest in TCM and natural remedies, further methodological improvements are necessary to enhance the credibility of future studies. This research highlights the importance of rigorously designed clinical trials in verifying the safety and efficacy of these alternative therapies, which may influence future therapeutic approaches for managing endometriosis.